Median lethal concentrations of amazonian plant extracts in the brine shrimp assay - Quignard, Etienne Louis Jacques; Nunomura, Sergio Massayoshi; Pohlit, Adrian Martin; Alecrim, Alexandre Mascarenhas; Pinto, Ana Cristina da Silva; Portela, Cíntia Nicácio; Oliveira, Laura Cristina Pereira de; Don, Luciana de Castro; Silva, Luiz Francisco Rocha e; Henrique, Marycleuma Campos; Santos, Mirian dos; Pinto, Patrícia de Souza; et al. (Pharmaceutical Biology, 2004)
In the current study, median lethal concentrations (LC50) were obtained in the brine shrimp assay (BSA) for 31 methanol and water plant extracts representing 21 Amazonian plant species, most of which are used in traditional medicine. The following species presented extracts with LC 50 values less than 50 μg/ml: Croton cajucara Benth., Micrandropsis scleroxylon W.A. Rodrigues, Piper aduncum L., P. hostmannianum (Miq.) C. DC., P. tuberculatum Jacq., Protium aracouchini (Aubl.) Marchand, and Tapura amazonica Poepp. The methanol extract of T. amazonica Poepp., a species known to be toxic according to ethnobotanic reports, was the most active (LC50 1.2 μg/ml). The data presented are considered useful as general toxicity parameters, and their relevance in the context of discovery of new antitumor agents and potential sources of (new) bioactive compounds in the Amazonian flora is discussed.
Keywords: Antineoplastic Agent; Aspidosperma Marcgravianum Extract; Aspidosperma Nitidum Extract; Aspidosperma Vargasii Extract; Cassia Fastuosa Extract; Croton Cajucara Extract; Geissospermum Argentum Extract; Micrandropsis Scleroxylon Extract; Minquartia Guianensis Extract; New Drug; Piper Aduncum Extract; Piper Baccans Extract; Piper Capitarianum Extract; Piper Crytopodon Extract; Piper Dilatatum Extract; Piper Erectipilum Extract; Piper Hostmannianum Extract; Piper Tuberculatum Extract; Plant Extract; Pothomorphe Peltata Extract; Protium Aracouchini Extract; Tabebuia Incana Extract; Tapura Amazonica Extract; Unclassified Drug; Brine Shrimp Assay; Croton; Drug Determination; Drug Screening; Ethnobotany; Lc50; Nonhuman; Piperaceae; Plant; Species; Toxicity Testing; Medicine, Traditional; Anostraca; Artemia; Artemia Franciscana; Aspidosperma; Cassia; Croton; Decapoda (crustacea); Geissospermum; Lepianthes Peltata; Piper Aduncum; Piper Dilatatum; Piper Swartzianum; Piperaceae; Pontoporia Blainvillei; Pothomorphe; Protium Aracouchini; Tabebuia; Tapura Amazonica